(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To characterize the quality of life of patients with esophageal cancer at Tan Trieu General Radiation Therapy Department, Hospital K, in 2024, both before and after radiation therapy. Subjects and Methods: The study used the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) to collect self-reported data from 102 patients with esophageal cancer before and after radiation therapy. Results: The average score in several functional domains was higher after radiation therapy compared to before (67,75). The general health score at that time was 53,56. The overall average quality of life across both research periods was 53 points. Conclusion: Patients with esophageal cancer have a poor quality of life both before and after radiation treatment.